Spectroscopic pigment identification in ornamentation tiles (XIII - XV ac) from Aveh, Qom and Masshad in Iran - Żmuda-Trzebiatowska, Iwona; Rudnicka, Małgorzata; Miśta, Ewelina; Kolbadinejad, Maryam; Lashkari, Arash; Kalbarczyk, Paweł; Włodarczyk, Damian; Śliwiński, Gerard (Photonics Letters of Poland, 2016)
In this work the Raman spectroscopy and complementary techniques are used to identify and compare pigment components in the ornamentation tiles excavated in archaeological sites of Aveh, Qom, and Masshad in Iran, which are dated for XIII – XV c. Results indicate on use of different blue pigments for production of tiles found in sites distanced by ca 100km, the usage of Fe oxide based ochre and red pigments in mixtures and confirm advanced luster technique with Pb-rich oxides and traces of corroded Ag. Full Text: PDF References J. Perez-Arantegui et al., "Materials and technological evolution of ancient cobalt-blue-decorated ceramics: Pigments and work patterns in tin-glazed objects from Aragon (Spain) from the 15th to the 18th century AD", J. Eur. Ceram. Soc. 29, 2499 (2009). CrossRef S. Coentro et al., "The Colors and Techniques of 17th Century Portuguese Azulejos: a Multi-Analytical Study", Microscopic Microanal. 17, 1782 (2011). CrossRef S. Gulzar et al., "Characterization of 17th Century Mughal tile glazes from Shahdara Complex, Lahore-Pakistan", J. Cult. Herit. 14, 174 (2013). CrossRef L. Kock, et al., "Raman analysis of ancient pigments on a tile from the Citadel of Algiers", Spectrochim. Acta A 4 1348(2008). CrossRef http://rruff.info/. DirectLink R. Clark, M. Curri, "The identification by Raman microscopy and X-ray diffraction of iron-oxide pigments and of the red pigments found on Italian pottery fragments", J. Mol. Struct. 440, 105 (1998). CrossRef I. Żmuda-Trzebiatowska et al., "Raman spectroscopic signatures of the yellow and ochre paints from artist palette of J. Matejko (1838–1893)", Spectrochim. Acta A 136, 793 (2015). CrossRef